Effects of Explants on Plant Regeneration and Concentration of Paclobutrazol on Morphological Responses of Dwarf Water Hyssop (Bacopa monnieri) - Tauk, Chanraksmey; Chuaduangpui, Pornpimon; Khawniam, Tassanee (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 3 (2021): July-September 2021DO - 10.14456/nujst.2021.26, 2021)
Water hyssop is an ornamental aquatic plant which is very popular among aquarium hobbyists. The present study reports on the effect of PBZ concentration on water hyssop to produce dwarf aquatic plants. The different types of explant were cultured on MS medium supplemented with 0.5 mg/L BA for shoot and root induction. The single nodal was cut and cultured on MS supplemented with various PBZ concentrations to produce the dwarf ornamental aquatic plant. The results showed that shoot induction started within 2 weeks and the maximum average number of shoots received from the node with leaf explant was 12.11 shoots after 4 weeks of culturing. The highest concentration at 40 mg/L of PBZ retarded stems, number of leaves, number of roots, root length, and the survival rate declined within 2 weeks of culturing. Only 2.5 mg/ L PBZ stimulated shoot induction at 51. 85%, but 20 mg/ L of PBZ the percentage of shoot induction of 48.15 was obtained. Shoot length did not increase after treating with 40 mg/ L of PBZ and also resulted in the lowest average number of leaves of 1.25 leaves. The maximum concentration of PBZ caused toxic reactions, such as yellowing, stunted leaves, short roots, and death of in vitro cultures. The shoot length decreased with increasing concentrations of PBZ. Thus, at 2.5 mg/ L of PBZ was suitable for producing dwarf water hyssop plant with the maximum shoot length, maximum number of leave and longest root. Finally, the dwarf plantlets were acclimatized successfully to 4 weeks in aquarium conditions.